Thrifty chic : interior style on a shoestring - Bauwens, Liz, 1952- 4 0 16; 1954- Campell, Alexandra.;Brown, Simon E.; 5 (London ;;New York : Cico Books, 2009)
Provides advice and photographs for decorating a home with vintage charm by using recycled or reclaimed furniture and materials, covering every room of the house and offering tips on buying from antique markets and thrift stores and restoring purchases.
Includes bibliographical references (p. 156-157) and index.
Adult;Adult
Keywords: 2 -- 0; 6; Interior decoration;Interior design -- Amateurs' manuals.;Handbooks, manuals, etc; 20; 2